Tradisi Ziarah Makam Masyayikh Pondok Pesantren Al Hikmah 2 (Teori Sakralitas Agama Emile Durkheim) - Riri Widyaningsih; Muhammad Abdul Hanif (Jurnal Living Hadis, 2017)
Pondok Pesantren or Islamic Boarding School is central to education, especially religious education. Pondok pesantren assessed as the most successful educational institutions in printing generation with great knowledge and morals. This is because Pondok Pesantren has a different teaching system with other educational institutions. That other system is the existence of a strong spiritual relationship between teachers and students in the sense of teaching science as well as educate the soul. This soul education is rarely found in other institutions. At Pondok Pesantren Al-Hikmah 2 Brebes, can be found one of the evidence of a strong spiritual relationship between teacher and student, that is the tradition of praying and pilgrimage to the graves of the masyayikh & muassis. This tradition is not only  the evidence for the strong relationship between teacher and student, but also as an aplication of hadith that transmitted by Tirmidzi. It is mentioned at the hadith narrated by Tirmidhi, that 'alims are prayed by God and all His creatures. This tradition is also considered as implementation of living hadith because applying the value of a hadith in everyday life. In this paper, the author wants to discuss the tradition of praying and pilgrimage based on the theory of the sacredness of Emile Durkheim. As for obtaining the data, the authors refer to the book and completed with an interview to one of the alumni of Pondok Pesantren Al-Hikmah 2 who ever practice this tradition.